THE USE OF MODERN TECHNOLOGIES IN LITERATURE LESSONS (Web of Teachers: Inderscience Research, 2024)
In computer science lessons, students gain both an idea of the possibilities of certain information and communication technologies, as well as specific practical skills. Therefore, the application of knowledge and skills acquired in computer science lessons is necessary in other subjects to ensure a single approach to solving educational tasks.